PENGUASAAN PENGETAHUAN KONSEPTUAL DAN PRAKTIS TENTANG TEORI BIAYA DAN IMPLIKASINYA DALAM BUDGETING - Masduki Masduki; Annisa Zauhar Nafisah; Beliya Wati; Heni Noviarita; Romlah Romlah (STKIP Pesisir Selatan, 2025)
Companies no longer rely solely on manual cost recording, but instead utilize cloud-based systems, Enterprise Resource Planning (ERP), and business intelligence that provide real-time cost information. With this technology, managers can quickly analyze cost deviations, measure product profitability, and even adjust production strategies based on the latest data.Mastery of cost theory and concepts is a fundamental aspect in the fields of accounting and management, yet its application in real-world contexts often encounters various challenges. The gap between theoretical understanding gained in academic settings and the practical needs of cost management has led both students and practitioners to face difficulties in accurately identifying and classifying costs. To bridge this gap, innovative learning methods are required, such as the use of business simulations, field case studies, and collaboration with industry. In addition, the integration of digital technology and modern accounting software is crucial to strengthen the curriculum and align it with the demands of the digital era. Therefore, the implementation of collaborative, practice-based, and technology-integrated approaches is expected to enhance the competence of students and practitioners in both understanding and applying cost theory effectively within business and organizational contexts.